A Trisymmetric Magnetic Microchip Surface for Free and Two‐Way Directional Movement of Magnetic Microbeads. Issue 22 (8th October 2018) - Sajjad, Umer; Lage, Enno; McCord, Jeffrey
Abstract: The guidance of labeled microcarriers in microfluidic environments is a prerequisite to the development of magnetic pattern assisted lab‐on‐chip technology. Square wave modulations of in‐plane applied magnetic fields enable the forward and backward locomotion of superparamagnetic microspheres on discrete hexagonally arranged ferromagnetic structures in a flowless microfluidic environment at a single bead level. By using distinct magnetic field sequences, selective directional transportation and two‐way separational motion of different ensembles of beads across a varying stray magnetic field pattern is achieved. Microbeads can be moved along different directions along spatial microcorridors. The demonstrated realization of multifunctional patterned magnetic surfaces enables the controlled positioning and sorting of mixed populations of functionalized microcarriers for biodiagnostic applications. Abstract : Multifunctional patterned magnetic surfaces enable flexible directional and two‐way lateral motion of superparamagnetic beads along spatial microcorridors in a 2D microfluidic environment. Square wave modulations of in‐plane applied magnetic fields form a variable stray magnetic field pattern for the size selective positioning and sorting of mixed populations of functionalized microcarriers for biodiagnostic applications.